Effect of pomelo (citrus grandis (l). osbeck) peel extract on lipid-carbohydrate metabolic enzymes and blood lipid, glucose parameters in experimental obese and diabetic mice - Lien, Do Ngoc; Quynh, Nguyen Thi Thuy; Phuc, Do Van; Phong, Vu Cong; Huong, Phung Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 26 No 4, 2010)
Abstract. The aim of this study was to assess the effects of Pomelo ( Citrus grandis (L.) Osbeck) peel extracts (CGE) on activity of lipid-carbohydrate metabolic enzymes such as Carnitine pamitoyl-transferase (CPT), lipase, hexokinase, glucose 6-phosphatase and blood lipid glucose parameters in experimental obese and diabetic mice. The results showed that, in the experimental obese mice treated daily, orally with CGE at dose of 1200 mg/body weight for three weeks, activity of hepatic CPT have been raised from 30.5% (for ethanol extract) to 63.3% (for ethyl acetate extract) compared to the control. Simultaneous increase of blood lipolytic activity was demonstrated in obese mice treated daily by CGE in comparison with the control. In addition, body weight reducing and hypolipidemic effect of the CGE in obese mice were proven clearly. Interestingly, the anti-diabetic effect of CGE in diabetic STZ induced mice was demonstrated. Fasting blood glucose levels in diabetic mice treated orally with CGE (1200 mg/kg.b.w) for three weeks were reduced clearly in comparison with the control (diabetic mice untreated) (p< 0.001). Especially, hepatic hexokinase activity in diabetic mice treated with CGE was raised from 14.19% (for ethanol extract) to 55.46% (for ethyl acetate extract) in comparison with the control (untreated diabetic mice). On the contrary, activity of hepatic glucose 6-phosphatase in treated diabetic mice was decreased clearly as compared to untreated diabetic mice (p<0.05). Keywords: Citrus grandis (L.) Obeck, blood glucose and lipid, obese and streptozotocin diabetic mice, hypolipidemic, anti-diabetic effect.